2010
DOI: 10.4141/cjss08057
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial neural network models to produce soil organic carbon content distribution maps across landscapes

Abstract: network models to produce soil organic carbon content distribution maps across landscapes. Can. J. Soil Sci. 90: 75Á87. Soil organic carbon (SOC) content is an important soil quality indicator that plays an important role in regulating physical, chemical and biological properties of soil. Field assessment of SOC is time consuming and expensive. It is difficult to obtain highresolution SOC distribution maps that are needed for landscape analysis of large areas. An artificial neural network (ANN) model was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Our results also showed a negative correlation (r= -0.15 and r=-0.19) for the soil layers at 0-20 cm and 20-40 cm, respectively, between SOCD and wetness index in the studied area. These results are in contrary to findings of other researchers (Zhao et al 2010;Schwanghart & Jarmer 2011). This may be related to the high vegetation density with low wetness index in the high elevation locations with lower human activities.…”
Section: Correlation Analysis Between Environmental Variables and Socdcontrasting
confidence: 86%
See 2 more Smart Citations
“…Our results also showed a negative correlation (r= -0.15 and r=-0.19) for the soil layers at 0-20 cm and 20-40 cm, respectively, between SOCD and wetness index in the studied area. These results are in contrary to findings of other researchers (Zhao et al 2010;Schwanghart & Jarmer 2011). This may be related to the high vegetation density with low wetness index in the high elevation locations with lower human activities.…”
Section: Correlation Analysis Between Environmental Variables and Socdcontrasting
confidence: 86%
“…The aspect did not show a high correlation coefficient with SOCD in Deylaman region. Zhao et al (2010) indicated similar results for the aspect, while they reported that slope had a high correlation coefficient (r=0.74) with the SOC content. Our results also showed a negative correlation (r= -0.15 and r=-0.19) for the soil layers at 0-20 cm and 20-40 cm, respectively, between SOCD and wetness index in the studied area.…”
Section: Correlation Analysis Between Environmental Variables and Socdsupporting
confidence: 70%
See 1 more Smart Citation
“…Predictive modelling of the spatial pattern of soil types and properties is based on a quasi-mechanistic understanding of soil formation and the factors that drive soil variation in the landscape, namely the ClORPT factors (Climate, Organic activity, Relief, Parent material and Time; Jenny, 1941). The relationships between soil forming factors and soil properties are complex and several non-linear modelling techniques have been employed to represent them including Random Forests (RFs) (Liaw and Wiener, 2002;Grimm et al, 2008;Wiesmeier et al, 2011) and Artificial Neural Networks (ANNs) (Agyare et al, 2007;Zhao et al, 2010). A principal disadvantage of these methods is that they are 'black-box', meaning that it is often difficult to interpret the relationship between response and predictor variables in physical terms (Suuster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, RK still displays a low prediction accuracy because of its weak analytical ability in non-linear relationships and layer structures between target data and multi-source auxiliary variables. Since the development of artificial intelligence and machine learning, neural networks (NN) have been used to solve the complex non-linear problems between soil properties and auxiliary variables, which results in a higher precision than when using classic linear methods [29][30][31]. However, traditional artificial neural networks (ANN) have a low implementation efficiency, which is needed to adjust the complex parameters from the algorithm structure and to avoid the influence of a locally optimal solution; in particular, they require a longer running time when the mapping resolution is increased.…”
Section: Introductionmentioning
confidence: 99%